2011
DOI: 10.1007/s13204-011-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the chemical composition at the memory behavior of Al/BST/SiO2/Si-gate-FET structure

Abstract: The effect of the chemical composition of the ferroelectric barium strontium titanate (BST) on the memory window behavior of Al/BST/SiO 2 /Si-gate-field effect transistor structure has been investigated. Nanocrystalline Ba x Sr 1-x TiO 3 thin films with different x values have been fabricated as metal-ferroelectric-insulator-semiconductor (MFIS) and metal-ferroelectric-metal (MFM) configurations using a sol-gel technique. The variation of the dielectric constant (e) and tan d with frequency for MFM samples hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Doping can greatly enhance certain properties of the resulting material including loss tangent [36,37], sensitivity [36], and dielectric dispersion [36]. With regard to operating temperatures of this material, works such as that by Nadaud et al in [33] have shown that deposited BST can exhibit permittivity changes as low as 2% between −75 • C and 100 • C. Furthermore, this work also demonstrates varactor operation at temperatures up to 200 • C. Further efforts are needed in characterizing the performance above this level, however this material can and has been deposited in-situ [31,36,38].…”
Section: Ferroelectric Materialsmentioning
confidence: 77%
See 2 more Smart Citations
“…Doping can greatly enhance certain properties of the resulting material including loss tangent [36,37], sensitivity [36], and dielectric dispersion [36]. With regard to operating temperatures of this material, works such as that by Nadaud et al in [33] have shown that deposited BST can exhibit permittivity changes as low as 2% between −75 • C and 100 • C. Furthermore, this work also demonstrates varactor operation at temperatures up to 200 • C. Further efforts are needed in characterizing the performance above this level, however this material can and has been deposited in-situ [31,36,38].…”
Section: Ferroelectric Materialsmentioning
confidence: 77%
“…Upon the application of an electric field, the permittivity of this material is reduced in the opposite plane, and this dependence has been modelled and characterized in numerous works including that by Wexler et al in [ 29 ] and by Wang in [ 30 ]. This material has already been used in a host of applications, including its use as a suitable FRAM material [ 31 ]. The hysteretic behavior governing the materials use in FRAM technology is temperature dependent and only occurs in the ferroelectric phase of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noted that the C-V curve is asymmetry around the voltage. Saif et al [21] and Masruroh & Toda [22] reported that this shift could be originated from existing an accumulated charge at the film/electrode interface, and could be also due to the variation of work function for the bottom and top electrodes. Furthermore, two maxima peaks for the CV curve forming a butterfly shape is observed, that are attributed to polarization switching as a response to the sweeping voltage for both forward and reversed bias.…”
Section: Resultsmentioning
confidence: 99%
“…Different ferroelectrics were investigated in the literature [12][13][14] but barium and strontium titanate, Ba x Sr 1−x TiO 3 (BST) remains one of the most studied compounds since, among others ferroelectrics, it presents low dielectric losses and one of the largest permittivity variation under applied direct current (dc) bias. The intrinsic dielectric characteristics of the BST material (the Curie temperature defining the particular ferroelectric or paraelectric state of the material at a given temperature, the material losses, the amplitude of permittivity variation under a given bias field) are related to its composition (i.e., the Ba/Sr ratio) and geometry [15,16].…”
Section: Introductionmentioning
confidence: 99%